2002
DOI: 10.1248/cpb.50.1265
|View full text |Cite
|
Sign up to set email alerts
|

New C 19-Diterpenoid Alkaloids from the Roots of Delphinium potaninii var. jiufengshanense.

Abstract: The plants Delphinium potaninii W. T. WANG and its variety D. potaninii var. jiufengshanense W. J. ZHANG et G. H. CHEN 1) grow in Sichuan province, China. Their roots are used as a folk medicine for rheumatism and neuralgia. Our investigations showed that these two plants contain mainly lycoctonine-type alkaloids.2-7) In a continuing search for new active alkaloids two new C 19 -diterpenoid alkaloids, jiufengdine (1) and jiufengtine (4), were isolated from the roots of D. potaninii var. jiufengshanense. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The IR spectrum indicated the absorption peaks for a carbonyl group (1710 cm −1 ), and aromatic ring (1609, 1592, 1515, 1452 cm −1 ). The NMR spectrum of 1 exhibited characteristic features of the aconitine-type C 19 -diterpenoid alkaloids, [10][11][12][13][14][15] bearing an N-ethyl group (δ H 1.01, 3H, t, J = 7.2 Hz; δ C 13.6 q, 49.3 t), and two methoxy groups (δ H 3.19, 3.32, each 3H, s; δ C 56.2 q, 56.4 q). Furthermore, the signals at δ Comparison of the MS and NMR spectra of 1 with those of the known brevicanine A 17) showed that these two compounds exhibited nearly identical 1 H-and 13 C-NMR resonances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR spectrum indicated the absorption peaks for a carbonyl group (1710 cm −1 ), and aromatic ring (1609, 1592, 1515, 1452 cm −1 ). The NMR spectrum of 1 exhibited characteristic features of the aconitine-type C 19 -diterpenoid alkaloids, [10][11][12][13][14][15] bearing an N-ethyl group (δ H 1.01, 3H, t, J = 7.2 Hz; δ C 13.6 q, 49.3 t), and two methoxy groups (δ H 3.19, 3.32, each 3H, s; δ C 56.2 q, 56.4 q). Furthermore, the signals at δ Comparison of the MS and NMR spectra of 1 with those of the known brevicanine A 17) showed that these two compounds exhibited nearly identical 1 H-and 13 C-NMR resonances.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic NMR data of 3 strongly suggested it to be an aconitine-type C 19diterpenoid alkaloid with a substitution at C-18 position. [10][11][12][13][14][15] The NMR spectrum (Table 1 18) The O-acetamidobenzoate moiety was located at C-18 on the basis of HMBC from H-18 (δ H 4.38/4.34, each 1H, ABq, J = 11.4 Hz) to OCO-18 (δ C 167.9, s). Thus, the structure of novolunine C (3) was assigned as 3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wang, which led to the discovery of three new hetisine-type C 20 -diterpenoid alkaloids bearing a N,O-mixed semiacetal moiety. Fourteen known diterpenoid alkaloids, named as delconine [5], delsoline [6], lycoctonine [7,8], delsemine A [8], delsemine B [8], deltatsine [9], anthranoyllycotonine [10], methyllycaconitine [11], delcosin [8,12], pacidine [13], 18-methoxygadesine [14], Jiufengtine [15], gigactonine [16], dehydrodelsoline [17], were isolated as well. This paper described the separation and structural elucidation of the new alkaloids.…”
mentioning
confidence: 99%